Effect of HIV status on fertility intention and contraceptive use among women in nine sub-Saharan African countries: evidence from Demographic and Health Surveys - Joyce N. Mumah; Abdhalah K. Ziraba; Estelle M. Sidze (Taylor & Francis Group, 2014)
Background: Expanding access to antiretroviral therapy (ART) means that HIV is no longer a death sentence. This change has implications for reproductive decisions and behaviors of HIV-infected individuals. Design: Using multiple rounds of biomarker data from Demographic and Health Surveys (2004-2012) in nine sub-Saharan African countries, we compare patterns of associations between HIV status and fertility intention and between current use of modern contraception and HIV status in the context of expanding ART coverage. Results: Generally, results show that knowledge of HIV status and proportion of women ever tested for HIV increased substantially between the two surveys for almost all countries. Whereas modern contraceptive use slightly increased, fertility intentions remained relatively stable, except for Rwanda, where they decreased. Results from the two surveys for the nine countries do however indicate that there is no clear consistent pattern of fertility intention and modern contraceptive use behavior by HIV status, with variations observed across countries. However, multivariate analyses show that for Rwanda and Zimbabwe women who were HIV positive, with knowledge of their status, had lower odds of wanting more children. Similarly only in Rwanda (both surveys) were HIV-positive women who knew their status more likely to be current users of contraception compared with women who were HIV negative. The reverse was observed for Zimbabwe. Conclusions: Generally, the results point to the fact that the assumption that reproductive intention and behavior of HIV-positive women will differ compared with that of HIV-negative women may only hold true to the extent that women know their HIV status. Continuous expansion of voluntary counseling and testing services and integration of HIV treatment and care services with reproductive health services are thus warranted.